Efeitos da Frequência Autocontrolada de Conhecimento de Resultados na Aprendizagem de uma Habilidade Motora com demanda de controle espacial em adultos com a Doença de Parkinson - Campos, Tiago Pereira (2011)
Parkinson Disease (PD) is a neurodegenerative disorder that compromises dopamine production. This situation leads to motor and non-motor dysfunction. Nowadays, there are not many researches involving DP, control and motor learning. The aim of this study was to investigate the effects of self-controlled frequency of knowledge of results (KR), in the acquisition of a motor ability, with demand for space control in adult subjects with Parkinson Disease. Twenty-two individuals, aged between 54 and 77 years, with DP were randomly divided into two groups. The self-controlled group received CR only in trials in which it was requested, while the externally controlled group received CR in the same way, subject by subject, of the self-controlled group. A task of linear displacement with a space target was used. The subjects performed the task with the dominant hand and blindfolded. During acquiring and retention stages, the objective was to place a traveler at a distance of 60cm from ground zero, and during transfer stage at 50cm. The hypothesis is that the self-controlled frequency of CR makes the learning more effective than the externally controlled group, similar to preview studies with subjects without Parkinson Disease. The results showed significant differences, benefiting the learning of the self-controlled group during the retention stage, which was performed without CR. This way, the benefits of self-controlled CR can make the motor learning of subjects with DP more effective, in a similar way to researches with individuals without neurological commitments.